1959
DOI: 10.1002/pol.1959.1204013603
|View full text |Cite
|
Sign up to set email alerts
|

Transient catalysts for the polymerization of organosiloxanes

Abstract: A study was made of the polymerization of siloxances with transient basic catalysts. These catalysts are active as polymerization catalysts for siloxanes and will decompose rapidly to inactive products at elevated temperatures with the formation of stable polymers. Several quaternary ammonium bases were studied as polymerization catalysts. It was found that bases such as tetramethylammonium hydroxide and benzyltrimethylammonium hydroxide were efficient catalysts. Similar bases having β‐hydrogen atoms decompose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 12 publications
0
70
0
Order By: Relevance
“…To some extent, in polymerization with complex counter-ions (tetramethylammonium silanolate, tetrabutylphosphonium silanolate [30]), advantage can also be taken of the differences in the' reactivity of D3 and linear or cyclic strainless siloxane molecules, since these bulky counter-ions are not able to be effectively solvated by polydimethylsiloxane molecules. These catalytic systems, lithium silanolates in particular, have very important practical applications, as they permit the synthesis of polydimethylsiloxane polymers and block copolymers, e.g.…”
Section: Kinetically Controlled Polymerizationmentioning
confidence: 99%
“…To some extent, in polymerization with complex counter-ions (tetramethylammonium silanolate, tetrabutylphosphonium silanolate [30]), advantage can also be taken of the differences in the' reactivity of D3 and linear or cyclic strainless siloxane molecules, since these bulky counter-ions are not able to be effectively solvated by polydimethylsiloxane molecules. These catalytic systems, lithium silanolates in particular, have very important practical applications, as they permit the synthesis of polydimethylsiloxane polymers and block copolymers, e.g.…”
Section: Kinetically Controlled Polymerizationmentioning
confidence: 99%
“…Thus, the usual need for catalyst neutralization and removal following polymerization is eliminated. They are often termed "transient" catalysts (34). They found that the rate of copolymer formation, the viscosity of the resulting copolymers, and the equilibrium yield of linear species all decreased regularly as the mole percent of phenyl tetramer was increased in the reaction mixture.…”
Section: S and Stockmayer's Equation For Cyclization Equilibrium Consmentioning
confidence: 99%
“…This time is believed sufficient to decompose the so-called transient catalyst (13) and thus inactivate the equilibration process.…”
Section: Equilibration Polymerization Of Epoxy Functional Disiloxanesmentioning
confidence: 99%